2018
DOI: 10.48084/etasr.1956
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Sulfidic Wastewater by Aeration in the Presence of Ultrasonic Vibration

Abstract: In the current study, the aerial oxidation of sodium sulfide in the presence of ultrasonic vibration is investigated. Sulfide analysis was carried out by the methylene blue method. Sodium sulfide is oxidized to elemental sulfur in the presence of ultrasonic vibration. The influence of air flow rate, initial sodium sulfide concentration and ultrasonic vibration intensity on the oxidation of sodium sulfide was investigated. The rate law equation regarding the oxidation of sulfide was determined from the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Distilled water was used to prepare the test solution. The analysis of sulfate was carried out by DR-5000 UV-visible spectrophotometer using barium chloride as a reagent [5][6][7][8].…”
Section: A Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Distilled water was used to prepare the test solution. The analysis of sulfate was carried out by DR-5000 UV-visible spectrophotometer using barium chloride as a reagent [5][6][7][8].…”
Section: A Materialsmentioning
confidence: 99%
“…SO4 + 5H + → ½S2O3 + 5/2H2O (6) Thiosulfates are stable in neutral or alkaline solutions, but not in acidic solutions, due to their decomposition to sulfite and sulfur, the sulfite being dehydrated to sulfur dioxide: S2O3 2− (aq) + 2H + (aq) → SO2(g) + S(s) + H2O (7) This phenomenon could cause a rise of water pH, increasing enrichment of S 2and S 0 in pore water, and finally plant death and inhibition of nitrification by sulfide toxicity, while the thiosulfates are a very aggressive species regarding metal corrosion. [2] Based on [3], it was found that the concentration of thiosulfate in refinery wastewater is about 174ppm and for other wastewater, the thiosulfate concentration is about 2050ppm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of vibration can reach the ultrasonic range and the material would have totally different vibration response. Authors in [7] studied the effect of ultrasonic vibrations on the material. The study of the vibration patterns in time and frequency domains has important applications in industry.…”
Section: Introductionmentioning
confidence: 99%